The Last Patron of Mikalojus Konstantinas Čiurlionis’s Work: New Touches to the Portrait of Bronisława Wolman - Gaidauskienė, Nida (Colloquia, 2025)
The Wolman family played an important role in Mikalojus Konstantinas Čiurlionis’s intellectual growth and his artistic self-realisation. From the end of 1904 until 1907, Bronisława Wolman took care of the artist’s livelihood and encouraged his creative aspirations. The literary salons held in the Wolmans’ apartment were important for the development of Čiurlionis’s worldview. With the support of this family, the artist visited the Crimea, the Caucasus, and the Beskids, and saw art collections in five Central European cities. Bronisława Wolman encouraged Čiurlionis to experiment and try himself in new areas, such as literature and photography. The artist expressed his gratitude for the support and encouragement through dedications. The artefacts and letters preserved by the Wolmans have enriched the artist’s oeuvre and his documentary legacy. The article provides additional information about Bronisława Wolman and her family, introduces new details of Čiurlionis’s biography, and delves into the specific circumstances in which democratic patronage took place. The publication is the result of research carried out in five archives outside of Lithuania. It summarizes primary sources using historical reconstruction and interpretive approaches.